Relationship Disease Management and Parenting Stress on Families Ability to Care For Schizophrenia - Iswanti, Dwi Indah; Motuho Mendrofa, Fery Agusman; Nursalam, Nursalam; Rizki Fitryasari; Kandar, Kandar (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2024)
Introduction: The inability of families to care for schizophrenia is caused by minimal knowledge and not having sufficient training or formal support. Families are frustrated and make it a burden to care for schizophrenia. The research aimed to determine the relationship between disease management and Parenting stress on the family's ability to care for schizophrenia. Method: Quantitative design with a cross-sectional approach was used. The sample size was 135 families caring for schizophrenia using a purposive sampling technique. The independent variable was disease management and parenting stress, and the dependent variable was the family's ability to care for schizophrenia. The disease management questionnaire was based on the concept of family empowerment by Zhou and Budi Anna Keliat. The parenting stress management questionnaire was developed from the neurobiology of stress concept from Murison, and the family ability questionnaire to care for schizophrenia uses the parenting Tasks in Caring for an Adult with Mental Illness Scale (CTiCAMIS). Data analysis used the Chi-square test with a level of 95%. Results: There was a relationship between disease management (p-value = 0.002 (<0.05)) and parenting stress (p-value = 0.000 (<0.05)) with the family's ability to care for schizophrenia patients. Conclusions: Disease management ability and parenting stress are closely related to the family's ability to care for schizophrenia. Efforts from mental health workers to provide education, training, and assistance are needed through family empowerment programs development to increase the family ability.